Addressing Challenging Mathematics Standards With At-Risk Learners: A Randomized Controlled Trial on the Effects of Fractions Intervention at Third Grade. (January 2021) - Fuchs, Lynn S.; Wang, Amber Y.; Preacher, Kristopher J.; Malone, Amelia S.; Fuchs, Douglas; Pachmayr, Rachel
The purposes of this study were to assess the effects of fractions intervention for students who are at risk for poor outcomes and to examine whether a component that combines self-regulated learning with growth-mindset instruction (SR-GM) provides added value for improving outcomes. At-risk students ( N = 84) were randomly assigned to three conditions: fractions intervention, fractions intervention with embedded SR-GM, and a control group. Intervention was conducted three times per week for 35 min per session for 13 weeks. Multilevel models indicated both fractions intervention conditions produced strong effects, with no added value for SR-GM. Posttest fractions achievement gaps for both intervention conditions held steady, narrowed, or closed, whereas the control group's gaps remained sizeable or grew. Results suggest that intervention can address challenging mathematics standards for at-risk learners and that SR-GM instruction may not be necessary in the context of strong intervention.